Respostas
respondido por:
3
a)
- x² + 3 = 0
- x² = - 3
x² = - 3/- 1
x² = 3
x = ± √3
x = 3, x = - 3
b)
4x² - 4x + 3 = 0
a = 4, b = - 4, c = 3
Δ = b² - 4ac
Δ = (- 4)² - 4 . 4 . 3
Δ = 16 - 48
Δ = - 32
x = (- b ± √Δ)/2a
x = (- (- 4) ± √(- 32))/2 . 4
x = (4 ± √32 . √(- 1))/8
x = (4 ± 4√2 . i)/8
x = (1 ± √2 . i)/2
x = (1 + √2 . i)/2
x = (1 - √2 . i)/2
- x² + 3 = 0
- x² = - 3
x² = - 3/- 1
x² = 3
x = ± √3
x = 3, x = - 3
b)
4x² - 4x + 3 = 0
a = 4, b = - 4, c = 3
Δ = b² - 4ac
Δ = (- 4)² - 4 . 4 . 3
Δ = 16 - 48
Δ = - 32
x = (- b ± √Δ)/2a
x = (- (- 4) ± √(- 32))/2 . 4
x = (4 ± √32 . √(- 1))/8
x = (4 ± 4√2 . i)/8
x = (1 ± √2 . i)/2
x = (1 + √2 . i)/2
x = (1 - √2 . i)/2
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás